2020
DOI: 10.3329/bjo.v24i1.45342
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Distribution of Carcinoma Larynx

Abstract: The larynx is the most common site for primary tumour of the head and neck region. It represents world wide approximately 1-2% of all cancers. A cross sectional study of 154 cases of laryngeal carcinoma was carried out in the in-patient department of Bangabandhu Sheikh Mujib Medical University and Dhaka Medical College during the period of two years with an aim to find out the frequency of site and subsite involvement of carcinoma of the larynx. The age range is 33-80 years and the over all male to female rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The mean age of the patients was 52.1 (± 4.6) Years Sex was the one of important sociodemographic factor of this study and the majority of the patients (91%) were male which may indicate less consumption of tobacco which is uncommon in female in this country. Studies 8,9 showed that male was the predominant sex as well. Though the result differs from other study 73%.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the patients was 52.1 (± 4.6) Years Sex was the one of important sociodemographic factor of this study and the majority of the patients (91%) were male which may indicate less consumption of tobacco which is uncommon in female in this country. Studies 8,9 showed that male was the predominant sex as well. Though the result differs from other study 73%.…”
Section: Resultsmentioning
confidence: 99%